Novel Pyran-Linked Phthalazinone-Pyrazole Hybrids: Synthesis, Cytotoxicity Evaluation, Molecular Modeling, and Descriptor Studies - Malik, M. Shaheer; Asghar, Basim H.; Syed, Riyaz; Alsantali, Reem I.; Morad, Moataz; Altass, Hatem M.; Moussa, Ziad; Althagafi, Ismail I.; Jassas, Rabab S.; Ahmed, Saleh A. (Frontiers in Chemistry, 2021)
A series of novel pyran linked phthalazinone-pyrazole hybrids were designed and synthesized by a facile one-pot three component reaction employing substituted phthalazinone, 1H-pyrazole-5-carbaldehyde and active methylene compounds. Optimization studies led to the identification of L-proline and ethanol as catalyst and solvent, respectively. This was followed by evaluation of anti-cancer activity against solid tumor cell lines of lung and cervical carcinoma that displayed IC50 values in the range of 9.8 to 41.6 µM. Molecular modeling studies were performed and crucial interactions with the target protein were identified. The drug likeliness nature of the compounds and molecular descriptors such as molecular flexibility, complexity and shape index were also calculated to understand the potential of the synthesized molecules to act as lead like molecule upon further detailed biological investigations as well as 3D-QSAR studies.